Review Paper on Filter Optimization 5G Technologies for FBMC Transceiver for High Power Amplifiers - Gaday, Rakhi; Gupta, Pooja; Gupta, Bharti (International Journal of Computer Sciences and Engineering, 2019)
Filter bank Multicarrier (FBMC) is a novel technique evolved from OFDM which resolves most of these problems by taking a filtering approach to multicarrier communication system. FBMC signals can easily meet the Adjacent Channel Leakage Ratio (ACLR) and they do not use cyclic prefix thus improves spectral efficiency. The Filter bank Multicarrier (FBMC) transmission technique also leads to enhanced physical layer for future communication systems and it is an enabling technology for cognitive radio environment. Due to the inclusion of band-limited pulse shaping filters into the signal model in FBMC technique, the design of efficient transceiver architectures for multicarrier systems becomes a challenging task. In this paper the studied of MIMO technique for FBMC transceiver for 5G technologies is presented.